Simultaneous determination of five essential amino acids in plasma of Hyperlipidemic subjects by UPLC-MS/MS - Chen, Zhibin; Lin, Feiyan; Ye, Xuemei; Dong, Yuqian; Hu, Lufeng; Huang, Aifang (Lipids in health and disease, 2020)
Millions of adults have been reported with hyperlipemia in the world. It is still unclear whether the plasma level of essential amino acids (AAs) will be influenced by the hyperlipemia. This study was aimed to investigate the AAs levels and the underlying metabolic relationship in hyperlipidemic subjects. An ultra-high performance liquid chromatography-tandem mass spectrometric (UPLC-MS/MS) method was developed for the determination of phenylalanine (Phe), valine (Val), histidine (His), tryptophan (Trp), and methionine (Met). Plasma samples (100 μL) were precipitated by acetonitrile (300 μL) and analyzed on a BEH C18 (2.1 mm × 100 mm, 1.7 μm) column at 40 °C by gradient elution. The mobile phase composed of 0.1% formic acid and acetonitrile was used with flow rate at 0.2-0.4 ml/0-3 min. Five AAs were determined at positive electrospray ionization (ESI+) at m/z 118.1/72.1 (Val), 150.12/104.02(Met), 156.06/110.05(His), 166.1/120.1(Phe), and 205.2/188.02 (Trp). A total of 75 healthy subjects and 83 hyperlipidemic subjects, who had blood routine test and plasma lipid test were determined by developed UPLC-MS/MS. It was shown that there was good linearity for Val, Met, His, Phe, and Trp within 1-100 μg/mL. The relative standard deviations of precision and accuracy were all within 15%. The level of Val, Phe, Trp, His, and Met were 35.34 ± 15.64, 22.72 ± 9.13, 17.23 ± 4.94, 16.78 ± 13.64, and 6.24 ± 1.97 μg/mL in healthy subjects, while they were 38.04 ± 16.70, 22.41 ± 8.45, 15.62 ± 5.77, 18.35 ± 14.49, and 6.21 ± 1.97 μg/mL in hyperlipidemic subjects respectively. The Spearman's correlations analysis showed that there were high correlations between Val, Phe, Trp, His, Met and triglyceride in healthy subjects. While, those correlations decreased in hyperlipemia cases. A convenient and sensitive method for simultaneous determination of Val, Phe, Trp, His, and Met in human plasma was developed. There was a high correlation between Val, Phe, Trp, His, Met and triglyceride. Hyperlipemia influences the metabolic balance of His, Phe, Trp, Met and Val.